Statistical theory : the relationship of probability, credibility and error - Hogben Lancelot, F.R.S. (New York : W.W. Norton, 1976)
This classic textbook is suitable for a first course in the theory of statistics for students with a background in calculus, multivariate calculus, and the elements of matrix algebra.
An examination of the contemporary crisis in statistical theory from a behaviourist viewpoint.
Includes index.
aia 25/9/17
Loans
Keywords: Mathematical statistics